Provision of free medical care in Russia and elsewhere: review of regulatory and legal aspects - A. N. Daikhes; D. V. Fedyaev (Фармакоэкономика)
The article reviews national and international publications on various issues of the free healthcare system. We present and discuss recommendations of the UN, the World Health Organization and the International Labor Organization on full coverage of the population with free medical care.